Analisis Pemilihan Aplikasi Pembayaran DANA - Eddy Madiono Sutanto; Yessica Yessica (Journal of Business & Banking, 2020)
Of the various types of e-wallet payments available, DANA is one of the fast growing payment applications in Indonesia. Within three a half month only it got half million users. What are the cause factors? Why do users like it? This study aimed to analyze quantitatively what factors influence consumers in using the DANA. It used confirmatory factor analysis model to test the model. It’s expected to contribute on e-wallet payment business strategy. The sampling technique used in this study was to use a questionnaire. The respondents are 100 who had used the DANA payment application. The obtained data were processed using the CFA factor analysis method (confirmatory analysis factor). The results show that there are three main factors that influence the choice of DANA payment applications including convenience, compatibility, and knowledge.